Ask a New Question
Search
Given f(x) = radical x-2 and g(x) = x2 – x – 6. Find (f – g)(6).
A. -26
B. 26
C. -22
D. 22
E. 2
Ask a New Question
or
answer this question
.
Similar Questions
Find the area of the rectangle shown in the figure.
length = radical (3) + radical (5) width = radical (3) + radical (5) My
0 answers
Simplify by combining like terms.
Problem #32 radical (63) - 2 radical (28) + 5 radical (7) My answer: 4radical(7) Problem #50
0 answers
Find the domain of the following functions.
1. y= radical(x-3) - radical(x+3) 2. y= [radical(2x-9)] / 2x+9 3. y= radical(x^2 - 5x
1 answer
solve the equation or formula for the indicated variable R=ts^2+3
a)s=under radical R-3/t (not under radical b)s=everything under
2 answers
more similar questions